A chloride capturing system via proton-induced structure transformation between opened- and closed-forms of dodecavanadates. Issue 18 (26th April 2016) - Inoue, Yoshitaka; Kikukawa, Yuji; Kuwajima, Sho; Hayashi, Yoshihito
Abstract : Reactivity of the incorporated chloride was controlled by the reversible structure transformation between two distinct structures of dodecavanadates. Abstract : Chloride-incorporated dodecavanadates show two distinct structures of the monoprotonated-form [HV12 O32 (Cl)] 4− (closed-V12 ) with a spherical closed-structure and the opened-form [V12 O32 (Cl)] 5− (opened-V12 ). The reaction ofclosed-V12 with a stoichiometric amount of ethylenediamine drives the structure transformation reaction toopened-V12, quantitatively. From time dependent observations of 51 V NMR, a tube-type intermediate [V12 O32 (Cl)] 5− (tube-V12 ) was observed in the transformation process. Isolation of the intermediate was achieved by the deprotonation reaction ofclosed-V12 with diethylamine, and the structure transformation was confirmed by using the isolated intermediate. The reverse transformation fromopened-V12 toclosed-V12 was also achieved by addition of trifluoroacetic acid. The geometrical difference betweenclosed-V12 andopened-V12 is reflected in the reactivity difference to the external reagents, and this was demonstrated by examining the chloride removal reaction by using a silver cation. The incorporated chloride was preserved in theclosed-V12 cage even in the presence of a silver cation. In contrast, the chloride inopened-V12 was removed as AgCl by the silver cation. In addition, by the reaction of chloride-freeopened-V12 with a quantitative amount of Et4 NCl retrievedopened-V12, showing the capability ofopened-V12 to recapture a guest chloride in the cavity. This transformation between two isomeric dodecavanadate structures is regarded as the movement of a molecular mitt to catch a ball and secure it.